Pengaruh Corporate Social Responsibility (CSR) dan Kepemilikan Institusional Terhadap Nilai Perusahaan (Survey Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018) - Annisa Desty Puspatriani (LPPM POLITEKNIK LP3I BANDUNG, 2022)
The aim of this research is to examine and analyze the effect of 1) corporate social responsibility to firm value, 2) institutional ownership to firm value, 3) corporate social responsibility and institutional ownership simultaneously to firm value Manufacturing Company Basic Industrial and Chemical Registered in Indonesian Stock Exchange in 2018. The population of this research is all the manufacturing companies basic industrial and chemical registered at Indonesian Stock Exchange in 2018. The sample of the research are used of purposive sampling method. They are 86 companies in 2018 which fulfilling criterion as this research sample. Data analysis technique used is multiple regression with measurement rasio. Result of research and result of data processing show that 1) positive effect not significant on corporate social responsibility to firm value, 2) negative effect not significant on institutional ownership to firm value, 3) corporate social responsibility and institutional ownership simultaneously not influence the firm value.